Probability Analysis for Waqf Fund as A Support Disaster Logistic Financing - Faza, Iqbal; Sekarningtyas, Hikmah (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Waqf is one of the Islamic social institutions that is highly recommended in Islamic teachings to be used by a person as a means of channeling the sustenance given to him by Allah. Waqf is also one of the instruments to create justice and prosperity in the economic field. When the waqf has been fulfilled, there is a change in ownership from private to community ownership which is expected to be lasting and provide sustainable benefits.On the other hand, Indonesia also has major challenges in the field of disaster mitigation. With all its natural potential, Indonesia has enormous disaster risks. The risk will always be there forever. For this reason, it is necessary to have an instrument that can be used at any time in the entire disaster management process. This potential is in waqf funds. This research tries to explore the possibility of waqf funds to be used as a means of disaster management, especially in terms of financing the procurement of disaster logistics during emergency response, recovery, rehabilitation and reconstruction which requires very large costs.